Digital Ethics Education: Preventing Cyberbullying and Supporting Mental Health in Elementary Schools - Ulfa Dilah; Suci Rahmadhani (Journal of Smart Pedagogy and Education, 2025)
This study addresses the escalating crisis of cyberbullying and its detrimental impact on the mental health of Indonesian elementary students in 2025. Utilizing a Systematic Literature Review (SLR) and bibliometric analysis of 73 core articles, the research examines how digital environments influence children’s moral reasoning through the theoretical lenses of Lawrence Kohlberg and Albert Bandura. Findings reveal that the "remoteness of harm" in digital spaces keeps students within a pre-conventional moral stage, leading to aggressive behaviors like denigration and AI-enhanced harassment. Data indicates that 19.2% of students practice school avoidance due to cyber-victimization, contributing to severe psychological risks. The study identifies a critical "ethical lag" in current curricula and advocates for a "whole-school approach" that integrates "Pancasila" values with Social-Emotional Learning. Results from localized interventions demonstrate that targeted resilience training can improve student coping mechanisms by 37%, providing a culturally relevant roadmap for fostering digital ethics and psychological safety.